Negotiating Identity: A Pilot Study on Cultural Identity, Belonging, and College Student Retention - Terron Phillips (Journal of College Orientation, Transition, and Retention)
Some minority/minoritized college student groups struggle to develop a sense of belonging – a factor in student attrition – at culturally homogenous U.S. colleges and universities. This pilot study tested the reliability and validity of the Cultural Responsivity Index (CRI), a quantitative data collection instrument designed to measure the cultural responsivity of students’ experiences and interactions within collegiate environments. Using the CRI, the researcher explored relationships between students’ self-reported cultural identities, structurally/culturally inflexible collegiate environments, and belonging. The researcher plans to conduct additional future research using the CRI toward further developing recommendations for higher education practitioners serving culturally diverse students.